2009
DOI: 10.1002/jez.b.21267
|View full text |Cite
|
Sign up to set email alerts
|

Localization and function of the anion exchanger Ae2 in developing teeth and orofacial bone in rodents

Abstract: To explore functions of anion exchanger 2 (Ae2) in the development of bones and teeth we examined the distribution of Ae2 in cells involved in formation of teeth and surrounding bone in young hamsters, mice and rats. In all three species strongest immunostaining for Ae2 was obtained in basolateral membranes of maturation ameloblasts and in osteoclasts resorbing bone. In hamsters a weaker staining was also seen in the Golgi apparatus of secretory ameloblasts, young osteoblasts and osteocytes, odontoblasts and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 28 publications
4
52
0
Order By: Relevance
“…In our data the labeling intensity of AE2 was markedly reduced in SA cells compared with RA cells in accordance with a weak or negative immunostaining of AE2 in SA bands of mouse incisors observed by Bronckers et al (5). In AE2 a,bdeficient mice, Lyaruu et al (25) have demonstrated that absence of AE2 a,b interferes with the final mineralization of enamel, resulting in less mineral and more protein than in wild-type enamel.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our data the labeling intensity of AE2 was markedly reduced in SA cells compared with RA cells in accordance with a weak or negative immunostaining of AE2 in SA bands of mouse incisors observed by Bronckers et al (5). In AE2 a,bdeficient mice, Lyaruu et al (25) have demonstrated that absence of AE2 a,b interferes with the final mineralization of enamel, resulting in less mineral and more protein than in wild-type enamel.…”
Section: Discussionsupporting
confidence: 93%
“…So far, few papers have dealt with the presence of a limited number of pumps, channels, or exchangers in the enamel organ (5,24,25,31,32,45).…”
Section: Discussionmentioning
confidence: 99%
“…The milder phenotype of Slc4a2a,b −/− mice could reflect compensatory expression of SLC4A2c, differences in genetic background, or discrepant functions for SLC4A2 isoforms in other skeletal cells or tissues with hormonal and metabolic effects on bone. Supporting this last possibility are observations that SLC4A2 is expressed and functional in osteoblasts, ameloblasts, and the gut and kidney (15)(16)(17)29). Taken together, these studies left uncertain the relative role of SLC4A2 within the osteoclast for its potential broader function in other cells involved in bone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Dewaxed and rehydrated paraffin sections were washed in Tris-buffered saline (TBS). Anti-Ae2 staining required retrieval in 10 mM citrate buffer (pH 6.0) overnight at 60ºC (Bronckers et al 2009). Staining in extracellular enamel matrix with anti-porcine amelogenins sections required retrieval in 0.5 mM EGTA in 10-mM Tris (pH 9.0) at 60°C for 5 h. Endogenous peroxidase was inactivated by 5-minute incubation in Dual Endogenous Enzyme Block (EnVision kit, DakoCytomation, Glostrup, Denmark), then washed in TBS and blocked with normal goat sera.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The mineral density was determined by microcomputed tomography (microCT), and the enamel composition by quantitative electron probe x-ray microanalysis (EPMA). Changes in pH in forming enamel were assessed by staining with methyl-red solution and immunolocalization of anion exchanger-2 (Ae2), a critical pH regulator in maturation ameloblasts (Bronckers et al 2009;Lyaruu et al 2014). …”
Section: Introductionmentioning
confidence: 99%